Understanding IPv6 resistance: A model of resistance among Indonesian organizations - Syamsuar, Dedy (Curtin University, 2015)
Since its inception in the 1970s, the Internet’s underlying protocol, IPv4, has been incredibly successful; however, the massive and unanticipated growth of the Internet has revealed its limitations. IPv6 was developed as a solution, but despite having many technological improvements its adoption remains very rare. This research examines organizational resistance to IPv6 and proposes an IPv6 Resistance Model which has been developed, empirically tested and validated in the context of Indonesian organizations.